Acts Of Intolerance In The Form Of Racism Towards The Papuan People That Occur Among The Public Or Students - Ariyanto, Faris Abqori; Azzahro, Emilda Ajeng Sekar; Sugiarti, Rifana Azmi; Mulyadi, Dadi; Maftuhin, Maftuhin (Jurnal Civicus, 2024)
The aim of this article is to raise awareness about the various and different languages of Indonesia. This means that we need to respect the differences that exist in Indonesia, including the differences that originate from Papua. Tolerance in Indonesia is still a problem, even though there are many slogans and calls for tolerance, the reality is that there are still many cases of intolerance, especially towards Papuans. Therefore, this article aims to invite all Indonesian people to be more tolerant towards Papuans. The method used in this article is a literature review by studying tolerance literacy, Papuan culture, and cases of intolerance towards Papuans. From the results of research through this literature study, it was found that cases of intolerance committed by non-Papuans towards Papuans have an impact on feelings of inferiority, lack of self-confidence, and feelings of being unappreciated by Papuans.